Inibição da respiração na luz em Coffea arabica L. cv. catuaí vermelho - Oliveira, Indira Pereira de (2022)
In this research, it was intended to do the detailing of the mechanisms of the respiratory process of plants, seeking the identification of the so-called kok effect, characterized by the inhibition of leaf respiration on light. This effect was first reported by Kok (1949), based on measurements made in algae and, since then it was observed in several species of plants, consisting of the abrupt change of quantum yield under low intensities of light, suggesting that light can changes gaseous exchanges between plant and atmosphere. In this way, it is important to understand the kok effect for the inclusion of the variation of leaf respiration under light and photorespiration in the estimates of plant production and the estimates of the carbon cycle of ecosystems. From this, the first chapter of this work consists of a review on the Kok effect and its importance for net carbon exchanges, also bringing a biochemical suggestion for a possible explanation of the apparent effect, with the intention of influencing future research. The second chapter brings a study carried out at the Universidade Federal de Lavras to describe the respiration under the light related to the different ages of leaves of Coffea arabica L. cv. Catuaí vermelho, seeking to identify the inhibition of respiration by the light on the young, mature and old leaves. For this, response curves were performed the net assimilatory rate due to luminous intensity (A-RAF), thus obtaining the net carbon assimilation rate, CO2 concentration and stomatal conductance. These gaseous exchanges were used in estimates of the degree of respiration inhibition by light on the leaves. It was observed that the rate of assimilation and quantum efficiency did not differ between young, mature and old leaves, however, respiration under light and under the dark were higher in young and mature leaves when compared to old leaves. Inhibition of respiration in light and similar form between the leaf ages occurred. This study is the first developed on the kok effect in the coffee crops and the results obtained will enhance understanding of coffee production from gaseous exchanges, since the Kok effect has potential application in agriculture, being a starting point for the creation of technology to increase the plants net primary productivity.